2021
DOI: 10.3390/ijms222011294
|View full text |Cite
|
Sign up to set email alerts
|

Light Tailoring: Impact of UV-C Irradiation on Biosynthesis, Physiognomies, and Clinical Activities of Morus macroura-Mediated Monometallic (Ag and ZnO) and Bimetallic (Ag–ZnO) Nanoparticles

Abstract: A nano-revolution based on the green synthesis of nanomaterials could affect all areas of human life, and nanotechnology represents a propitious platform for various biomedical applications. During the synthesis of nanoparticles, various factors can control their physiognomies and clinical activities. Light is one of the major physical factors that can play an important role in tuning/refining the properties of nanoparticles. In this study, biocompatible monometallic (AgNPs and ZnONPs) and bimetallic Ag–ZnONPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
0
10
1
Order By: Relevance
“…Nanomedicine is the use of nanotechnology in the treatment, screening, and diagnosis of a variety of diseases, including cancer [ 10 , 11 , 12 , 47 ]. It adds complete procedures and effective approaches against cancer through cancer prediction and diagnostics, prevention and medication, as well as possible individualized therapy [ 10 , 12 ].…”
Section: Applications Of Plant-derived Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomedicine is the use of nanotechnology in the treatment, screening, and diagnosis of a variety of diseases, including cancer [ 10 , 11 , 12 , 47 ]. It adds complete procedures and effective approaches against cancer through cancer prediction and diagnostics, prevention and medication, as well as possible individualized therapy [ 10 , 12 ].…”
Section: Applications Of Plant-derived Npsmentioning
confidence: 99%
“…Similarly, green AuNPs produced from a Trachyspermum ammi seed extract inhibited cellular growth in HepG2 cancer cell lines in a concentration-dependent manner, which was linked to a reactive oxygen species (ROS)-driven apoptosis [ 37 ]. This mechanism has recently been reported to be potentially connected to mitochondrial action via ROS-induced Caspase-3 gene expression and enzyme activity following mitochondrial membrane potential disruption caused by plant-based NPs [ 11 , 47 ].…”
Section: Applications Of Plant-derived Npsmentioning
confidence: 99%
“…Previously, peaks at 355 nm and 450 nm were observed for bimetallic ZnO-AgNPs from UV-visible spectroscopy. 39 Moreover, two characteristic SPR band between 400-480 nm and 350 and 380 nm were reported for bimetallic Ag-ZnONPs by Anjum et al 40 when synthesized from Morus macroura leaf extract.…”
Section: Characterization Of Bnpsmentioning
confidence: 93%
“…Artocarpus heterophyllus extract prepared Ag-Au NPs showed LC 50 value < 1000 mg mL À1 making them non-toxic. 74 Previously Anjum et al 40 also demonstrated moderately toxic nature of Morus macroura mediated Ag-ZnO BNPs as well as their monometallic counterparts towards brine shrimps. These ndings show a hidden efficacy of green synthesized bimetallic NPs for applications like antioxidant, anti-cancerous and antimicrobial.…”
Section: Biological Activities Of Bimetallic Npsmentioning
confidence: 97%
“…The activation of the caspase cascade via the intrinsic mitochondrial pathway involves caspases 3 and 7, which are executioner caspases. 77 78 The increase in the level of effector caspase-3 activity was two-fold higher in MCF-7 breast cancer cells when treated with spherical-shaped green-synthesized AgNPs (10-60 nm) compared to the control. 79 AgNPs mediate cytotoxicity by effectively activating the caspase cascade and induce apoptosis in various cancer cells.…”
Section: Orac Assaymentioning
confidence: 98%